Thermodynamic performance evaluation of a steam turbine at kamojang geothermal power plant using operational data - Firmansyah Firmansyah; Fahrudin Fahrudin; Damora Rhakasywi; Regina Natalindah Lumbantoruan; Fazli Iqbal Pasha; Putty Fauthyda Zahra Hapidzha (Jurnal Polimesin, 2026)
Geothermal power plants play a significant role in sustainable energy systems due to their ability to provide stable baseload electricity with relatively low carbon emissions. This study investigates the thermodynamic performance of the steam turbine at Kamojang Geothermal Power Plant Unit X using operational data collected over 29 days and processed into 6-hour averages to represent the local operating envelope around the turbine design point. A multiple linear regression model was developed to evaluate the effects of steam mass flow rate, inlet steam pressure, inlet steam temperature, and condenser pressure on turbine isentropic efficiency. The results indicate that inlet steam pressure, inlet steam temperature, and condenser pressure significantly influence turbine efficiency, whereas steam mass flow rate has no significant effect. The model explains 43.8% of the variation in turbine isentropic efficiency (R²=0.438) and yields a low in-sample prediction error (MAPE=0.12%), indicating that the regression closely reproduces the observed data within the limited operating range. In contrast, a considerable portion of the variation remains unexplained. Condenser pressure was identified as the dominant influencing parameter. These findings suggest that local deviations from the design point may contribute to off-design operation and additional thermodynamic irreversibility, providing practical implications for performance monitoring and operational optimization in geothermal power plants.